Primary and revision stapes surgery: A comparative study of surgical results and predictive factors for revision surgery - Azevedo, Cátia (2020)
Aims: To compare the hearing outcomes and complications after primary and revision stapes surgery and establish possible predictors for revision surgery. Study Design: Descriptive and analytical cross-sectional study, with retrospective data collection. Methods: Patients were selected from a pool of patients who underwent stapes surgery in the past 12 years and divided into two groups: a group consisting of 178 ears that just underwent one stapes surgery (group A) and 22 ears that were identified as having undergone revision surgery for otosclerosis (group B). Results: Improvement in hearing was significant in both groups. However, in group B the postoperative air-bone gap (ABG) was, on average, 10.4 dB higher than in group A (p <0.05). We achieved surgical success in 52.8% and 27.3% of cases in group A and group B, respectively. The absence of erosion of the long process of the incus and younger ages in revision stapes surgery were associated with better hearing outcomes. Additionally, patient’s age, preoperative and postoperative ABG in prior otosclerosis surgery proved to be independent predictors for revision surgery. Conclusions: When there is the need for a revision stapes surgery, improvement in hearing can be achieved, without a significant increase in postoperative complications. However, surgical planning and expectations management are mandatory before planning revision surgery for otosclerosis.